Where are the ghosts?: The invisible as a linguistic signifier - Suárez, Edgar (2023)
Lexical semantics argues that, in communication, there is a linguistic code that, when encrypted, allows us to understand how the meanings of a word are structured and act according to its level of arbitrariness. Now, this article deals with the meanings and uses of the word ghost, which is the result of a metaoperation that is constituted in an image (cognitive base), as it becomes an image (communicative operation) between the signifier and the signified. The conceptualization of our ghosts reveals, with respect to our common sense, a response of their significance in the brain associated with ideas that in language are conceived from a positive, neutral, or negative character. Therefore, invisibility is a possible response to their magical contact with nature and to a superstitious knowledge that opposes the dominant power of linguistically organized knowledge. The purpose of this article is to explore, from psychoanalysis, a way of looking at ghosts as a signifying creation in language (from the outside, inwards), especially as a point of attachment to the semiotic processes that allow the creation of cultural terminologies from an anthropological, artistic, and emotionally aesthetic perspective.